2023
DOI: 10.1039/d2sm01571d
|View full text |Cite
|
Sign up to set email alerts
|

Elastoplastic behavior of anisotropic, physically crosslinked hydrogel networks comprising stiff, charged fibrils in an electrolyte

Abstract: Fibrillar hydrogels are remarkably stiff, low-density networks that can hold vast amounts of water. These hydrogels can easily be made anisotropic by orienting the fibrils using different methods. Unlike the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…As fibrillar hydrogels are very different from polymeric hydrogels, it is crucial to know the relationship between fibril dimensions and mechanical properties and mesh size of the network. Kumacheva et al [34] and Benselfelt et al [35] reported the relationship between fibrillar hydrogels and their mechanical properties in this context. Based on the dimensions of the fibrils and their concentration, the mesh size can be estimated, but this is beyond the scope of this manuscript.…”
Section: Resultsmentioning
confidence: 94%
“…As fibrillar hydrogels are very different from polymeric hydrogels, it is crucial to know the relationship between fibril dimensions and mechanical properties and mesh size of the network. Kumacheva et al [34] and Benselfelt et al [35] reported the relationship between fibrillar hydrogels and their mechanical properties in this context. Based on the dimensions of the fibrils and their concentration, the mesh size can be estimated, but this is beyond the scope of this manuscript.…”
Section: Resultsmentioning
confidence: 94%
“…Our model describes the swelling pressure induced by the changed chemical potential when mixing the gel constituents with the solvent (P chem ) and the elastoplastic resistance during the expansion of the network (P net ). For polymer networks, an entropy elastic Gaussian chain model can be used, [10] but there is not yet a quantitative model for enthalpy elastic nanoparticle networks; these are qualitatively described by the initial bending of fibrils under pressure followed by a plastic stick-slip-stick behavior as previously described by Mittal et al and Östmans et al [17,18] In our electroactive nanoparticle gel model (see Supporting Information), P chem is divided into the terms P mix, the free energy of mixing contributing to passive swelling, and P ion , the osmotic pressure from the chemical and electrochemical charge inside the hydrogel:…”
Section: Resultsmentioning
confidence: 99%
“…and Östmans et al. [ 17,18 ] In our electroactive nanoparticle gel model (see Supporting Information), P chem is divided into the terms P mix , the free energy of mixing contributing to passive swelling, and P ion , the osmotic pressure from the chemical and electrochemical charge inside the hydrogel: Pionbadbreak=RT()φ1αQCNFV+φ2QCNTVφ32csol$$\begin{equation} {P}_{\mathrm{ion}}=\textit{RT}\left(\frac{{\varphi}_{1}\alpha {Q}_{\mathrm{CNF}}}{V}+\frac{{\varphi}_{2}{Q}_{\mathrm{CNT}}}{V}-{\varphi}_{3}2{c}_{\mathrm{sol}}\right) \end{equation}$$where R is the gas constant, T is the absolute temperature, Q is the molar charge associated with the CNFs or CNTs including counterions, α is the degree of dissociation/association of the titrating groups of the CNFs, φn${\varphi}_{n}$ are the osmotic coefficients with the subscript describing different ion‐pairs, V is the volume of the hydrogel, and c sol the molar concentration of the electrolyte multiplied by 2 to account for both ions in the pair. Equation () shows how QCNF${Q}_{\mathrm{CNF}}$, QCNT${Q}_{\mathrm{CNT}}$, or csol${c}_{\mathrm{sol}}$ control the osmotic pressure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation